Material and characteristics analysis of a carbon fiber badminton shuttle by using a wind tunnel - Yeh, J.-T.; Chen, W.-J. (Sensors and Materials, 2021)
Badminton has long been a popular sport for all ages. However, owing to the high wearing rate of shuttles, this sport is not considered to be environmentally friendly. To mitigate this problem and improve the durability of shuttles, many manufacturers have been researching and developing synthetic shuttles. Different from most of the synthetic shuttles with plastic skirts, the one produced by VICTOR is made of a carbon fiber and foam material for the shaft and the vane of the feathers. The aim of this study is to determine the characteristics of such a carbon fiber shuttle. Because the flying speed of a shuttle is the fastest among all ball-type sports, the aerodynamic performance of shuttles has mainly been considered in academic studies. A wind tunnel is one of the best ways to evaluate the aerodynamic characteristics of a shuttle. For this reason, in addition to inviting players for actual badminton games and using other tools or instruments for measuring, testing, and comparison purposes, we used a small custom-made wind tunnel with an airspeed sensor unit and tension measurement meter to collect data from natural feather shuttles and synthetic shuttles, especially from carbon fiber shuttles. The main purpose of this paper is to introduce the implementation of a wind tunnel to evaluate different types of shuttles.